1987
DOI: 10.1152/ajpgi.1987.252.1.g84
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell membrane solubilization may control maximum secretory rate of cholic acid in the rat

Abstract: The factors modulating the maximum secretory rate of cholic acid were investigated. Rats were infused intravenously with cholic acid in measured stepwise increasing doses (1, 2, 3, and 4 mumol X min-1 X 100 g body wt-1). Each dose was infused for 30 min and bile samples were collected every 10 min. Bile flow, bile acid, cholesterol, individual biliary phospholipids, and the fatty acid profiles of the biliary phospholipids were determined. Microsomal and bile canalicular membrane-enriched fractions were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 0 publications
0
32
1
Order By: Relevance
“…The amount of PC secreted into bile is influenced by several factors (20): 1) the intracanalicular bile salt concentration (21,22); 2) the hydrophobicity of the intracanalicular bile salts (23); 3) the magnitude of the bile salt-independent fraction of the bile flow (24); 4) the concentration of hydrophilic organic anions (25); 5) the abundance of Mdr2 at the bile canalicular membrane (3,16,26); and 6) the lipid composition of the bile canalicular membrane (27)(28)(29)(30). Taurocholate feeding did not induce detectable changes in Mdr2 mRNA or protein levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of PC secreted into bile is influenced by several factors (20): 1) the intracanalicular bile salt concentration (21,22); 2) the hydrophobicity of the intracanalicular bile salts (23); 3) the magnitude of the bile salt-independent fraction of the bile flow (24); 4) the concentration of hydrophilic organic anions (25); 5) the abundance of Mdr2 at the bile canalicular membrane (3,16,26); and 6) the lipid composition of the bile canalicular membrane (27)(28)(29)(30). Taurocholate feeding did not induce detectable changes in Mdr2 mRNA or protein levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the infusion of hydrophobic BSs, typically PL secretion declined first, followed by decreases in bile flow, BS output, and cholesterol output. Concomitantly with the decline in PL output, the PL composition changed from mainly phosphatidylcholine to more phosphatidylethanolamine and sphingomyelins, which was attributed to partial solubilization of the canalicular membrane (38). On the basis of these results, these authors concluded that an insufficient supply of phosphatidylcholine to the canalicular plasma membrane was the cause of BS-induced cholestasis.…”
Section: Bladder Of Abcg5mentioning
confidence: 95%
“…Several studies describe a hyperbolic relationship between bile salt secretion and phospholipid or cholesterol secretion [6,10]. An increase in bile salt output leads to an increase in phospholipid and cholesterol secretion until a certain plateau is reached [11,12]. Furthermore, it has become Abbreviations used : GADPH, glyceraldehyde-3-phosphate dehydrogenase ; Pgp, P-glycoprotein ; TUDC, tauroursodeoxycholate ; UDC, ursodeoxycholate.…”
Section: Introductionmentioning
confidence: 99%